Auditoría de gestión del proceso de comercialización / facturación y distribución de combustible de la empresa Disa S.A. - Aguilar Galarza, Angel Israel (My University, 2021)
Fuel trading companies require an adequate assessment of their processes, in addition to a control model and the development of a management audit, the absence of this can cause a high level of risks, which can harm organizational interests, affect compliance with the procedures carried out in the different departments such as billing, marketing, financial, among others, as a consequence the need for a management audit arises in their processes, this is intended to take advantage of all the resources of the company adequately, be these human, technological, financial, thus reducing costs, while improving financial performance, this is possible through the generation of action plans and procedures that aim to achieve the proposed objectives, based on the context, the objective of this work was to evaluate the commercialization processes of co Fuel in the company Diésel industrial DISA SA through the use of management indicators and an audit in the areas of marketing, billing and distribution that allows the identification of problems in compliance with the processes developed; For this, a bibliographic research of the variables was used, it is also a quantitative and qualitative research, it is mainly based on the use of quantitative methods, that is, it seeks to quantify the economic situation as the main object of study of the subject, social practices are also analyzed; The company has a certain degree of organization, however, in the different areas evaluated it was possible to detect some shortcomings, among these, the lack of planning, which does not allow it to achieve its objectives, in the company DISA SA, procedures have not been proposed For the control of the accounting movement of the accounts that are part of the statement of financial position, control means have not been established that allow determining income and expenses, there are no control procedures for the inflows and outflows of cash, in the company DISA SA , performance evaluations are not carried out on human talent, not all employees have the preparation according to the functions they perform. After conducting the management audit of the company DISA SA, it is possible to conclude that through the management audit it was possible to detect the internal shortcomings in the different areas analyzed, the situation of the company is feasible to be improved, more than anything. regarding the organizational issue. After conducting the surveys, it was possible to detect shortcomings such as duplicity in functions, this causes loss of efficiency in the management of resources, be they economic and material. There are still personnel in the company who do not have adequate training to perform the functions assigned to the job, this was possible to determine through surveys of work personnel. Based on the conclusions obtained, it is possible to make the following recommendation: in order to safeguard the business situation, the company DISA S.A. should maintain the level of indebtedness and preferably reduce it, in this way so that this indicator does not exceed 70%, so as not to compromise other factors of the organization, it is also recommended to make improvements in terms of human talent, implement internal control standards , which can be very useful to guarantee the validity of the information presented in the financial statements. An important recommendation is undoubtedly to train 100% of the personnel that works within the organization, this will allow them to fulfill their functions efficiently.
Las empresas comercializadoras de combustible requieren de una adecuada valoración de sus procesos, además de un modelo de control y el desarrollo de una auditoría de gestión, la ausencia de esta puede ocasionar un alto nivel de riesgos, los cuales pueden perjudicar a los intereses organizacionales, afectar en el cumplimiento de procedimientos que se realizan en los diferentes departamentos como son de facturación, comercialización, financiero, entre otros, como consecuencia surge la necesidad de la auditoría de gestión en sus procesos, esta tiene como propósito aprovechar todos los recursos de la empresa de manera adecuada, sean estos humanos, tecnológicos, financieros, reduciendo así costos, al mismo tiempo que se mejora el rendimiento financiero, esto es posible mediante la generación de planes de acción y procedimientos que tengan como finalidad alcanzar los objetivos propuestos, con base en el contexto, el objetivo de este trabajo fue evaluar los procesos de comercialización de combustible en la empresa Diésel industrial DISA SA mediante el uso de indicadores de gestión y una auditoría en las áreas de comercialización, facturación y distribución que permita la identificación de problemas en el cumplimiento de los procesos desarrollados; para esto se recurrió a realizar una investigación bibliográfica de las variables, además se trata de una investigación de tipo cuantitativo y cualitativo, se fundamenta principalmente en el uso de métodos cuantitativos, es decir, se busca cuantificar la situación económica como objeto de estudio principal de la asignatura, también se analizan las prácticas sociales; la empresa tiene cierto grado de organización, sin embargo, en las diferentes áreas evaluadas fue posible detectar algunas falencias, entre estas, la falta de planificación, lo cual no le permite alcanzar sus objetivos, en la empresa DISA S.A., no se han planteado procedimientos para el control del movimiento contable de las cuentas que son parte del estado de situación financiera, no se han establecido medios de control que permitan determinar ingresos y gastos, no existen procedimientos de control para las entradas y salidas de efectivo, en la empresa DISA S.A., no se realizan evaluaciones del desempeño al talento humano, no todos los empleados cuentan con la preparación acorde con las funciones que desempeñan. Luego de realizada la auditoría de gestión de la empresa DISA S.A., es posible concluir que por medio de la auditoría de gestión se pudo detectar las falencias internas en las diferentes áreas analizadas, la situación de la empresa es factible de ser mejorada, más que todo en lo referente al tema organizacional. Luego de realizadas las encuestas fue posible detectar falencias como es la duplicidad en las funciones, esto ocasiona pérdida de la eficiencia en el manejo de los recursos, sean estos económicos y materiales. Existe todavía en la empresa personal que no cuenta con la capacitación adecuada para desempeñar las funciones asignadas para el puesto de trabajo, esto fue posible determinar mediante encuestas al personal de trabajo. Con base en las conclusiones obtenidas, es posible plantear la siguiente recomendación: con la finalidad de precautelar la situación empresarial, la empresa DISA S.A. deberá mantener el nivel de endeudamiento y de preferencia disminuirlo, de esta manera para que este indicador no supere el 70%, para no comprometer a otros factores de la organización, también se recomienda hacer mejoras en cuanto al talento humano, implementar normas de control interno, las cuales pueden ser de mucha utilidad para garantizar la validez de la información que se presenta en los estados financieros. Una recomendación importante es sin duda la de capacitar al 100% del personal que trabaja dentro de la organización, esto permitirá que cumplan con sus funciones de manera eficiente.
Keywords: AUDITORÍA DE GESTIÓN; PATRIMONIO